A People's Green New Deal: Obstacles and Prospects. (August 2021) - Ajl, Max
Within the past years, the Green New Deal (GND) became the common language for Northern climate politics, offering a seeming exit path from Northern social and ecological crises while erasing an older Northern climate discourse tied to Southern demands for climate reparations and rights to development. This Eurocentric GND has become the environmental program for an equally Eurocentric social democratic renewal. This article situates the GND in world-systemic shifts, and Northern reactions to such shifts. It situates the GND as one of three possible Eurocentric solutions to the climate crisis: a great elite transformation from above; a left-liberal "reformist" resolution; a social democratic resolution. It then elaborates a possible "People's Green New Deal, " a revolutionary transformation focused on state sovereignty, climate debt, auto-centered development, and agriculture. Within each proposed resolution, it traces the role of the land, agriculture, and peasants.